THE HETEROPLASMIC AND HOMOPLASMIC STATES OF MITOCHONDRIAL AND CHLOROPLAST DNA REGIONS IN THE PROGENIES OF WIDE HYBRIDS OF COMMON WHEAT OF DIFFERENT ORIGINS - N. V. Trubacheeva; L. A. Kravtsova; E. P. Devyatkina; T. T. Efremova; M. G. Sinyavskaya; V. K. Shumny; L. A. Pershina (Вавиловский журнал генетики и селекции)
The states of the 18S/5S mitochondrial (mt) repeat and some chloroplast DNA regions have been studied in alloplasmic lines of common wheat with cytoplasm from barley species Hordeum marinum subsp. gussoneanum Hudson and H. vulgare L., and in progenies of reciprocal hybrids between Triticum aestivum L. and Secale cereale L. The heteroplasmic state of the 18S/5S repeat, which was a result of biparental mtDNA transmission, is observed in rye × wheat hybrids and in their progenies possessing rye cytoplasm. For the first time, the heteroplasmic state of chloroplast DNA associated with heteroplasmy of the 18S/5S mt repeat has been detected in cereals by using alloplasmic wheat lines. It has been found that the transition of mt- and cpDNA heteroplasmy, barley homoplasmy of chloroplast regions to wheat homoplasmy is associated with complete fertility restoration and barley chromosome elimination from the newly developed nuclear genomes of alloplasmic lines.